An assessment methodology of sustainable energy transition scenarios for realizing energy neutral neighborhoods. (15th October 2018) - Walker, Shalika; Labeodan, Timilehin; Boxem, Gert; Maassen, Wim; Zeiler, Wim
Highlights: Scenario assessment method for realizing energy neutral neighborhoods is proposed. A deterministic assessment is carried out to predict future demand variations. Suggested LCPD based indicators provide valuable insights to decision-makers. Monte Carlo simulations investigate uncertainty of the decision-maker's choice. A case study in the Netherlands to validate the methodology is demonstrated. Abstract: Increasing demand for energy and emphasis on environmental sustainability has started to revolutionize the existing energy infrastructure within the built environment. In parallel, more distributed energy systems are rapidly springing up. These changes inevitably influence the design, operation and management of buildings. Recently, the energy and environmental evaluation of buildings for long-term decision-making and planning has shifted the boundaries from single buildings towards neighborhood scale. This is because buildings as a cluster can enhance the incorporation of distributed energy systems when realizing energy neutrality in the long run. However, when assessing the energy and environmental performance of infrastructural developments at the neighborhood level, the life-cycle aspect of energy systems is rarely considered. To understand the overall impacts from production to end-of-life stage, it is essential to assess the energy and environmental performance of clean energy initiatives from a life-cycle perspective. This paper proposes a novel decision support methodology by means of life cycle performance design-based approach to facilitate the planning process to realize energy neutral neighborhoods. The assessment methodology is developed based on scenario analysis through computational simulations. This is followed by a deterministic evaluation and the results let the decision-makers to select a suitable clean energy development scenario. The uncertainty of the selected scenario is scrutinized by performing a probabilistic sensitivity analysis using Monte Carlo simulations. A pragmatic case study has been analyzed and the results demonstrate the feasibility of exercising the proposed methodology in practice. The recommendations and limitations of realizing energy neutral neighborhoods are depicted subsequently.